Experiences of Female Migrants in the Informal Sector Businesses in the Cape Coast Metropolis: Is Target 8.8 of the SDG 8 Achievable in Ghana? - Achana, Fabian Sebastian; Tanle, Augustine (African Human Mobility Review, 2021)
Situated within the neoclassical micro-economic and migration networks theories,this study used in-depth interviews to explore the circumstances, lived experiences,risk and vulnerabilities of female migrants in selected informal sector businesses in theCape Coast Metropolis of Ghana. The data was processed and analyzed thematicallyusing the QSR Nvivo qualitative software version 11. Participants reported varied andcomplex lived experiences. Poverty, the search for employment, parental irresponsibilityand marital instability were the dominant explanations for their decisions to migrate.Most participants intimated that their health and economic rights were often violated,that they endured verbal abuse, physical injury, sexual harassment, and were compelledto work even when sick. Their daily or monthly earnings were at the mercy of theiremployers, and their work, living and sleeping environments were unsafe. Consideringthat these findings reflect what generally prevails in other parts of the country, Ghana isunlikely to achieve Target 8.8 of the Sustainable Development Goal 8. There is thereforean urgent need to enforce the relevant laws and policies to protect the fundamentalhuman rights, safety, health and well-being of females in these and similar livelihoodactivities in Ghana.